Управление страховым резервом предприятия на основе портфельного инвестирования (Путеводитель предпринимателя)
In work the question of management of an insurance reserve of an industrial enterprise by force of an investment portfolio's formation composed of highly marketable shares is considered. Economic and mathematical target-setting, as well as examples of portfolios calculated for various categories of non-institutional investors are presented.